The Effect of Ladder Drill and Cone Drill Training on The Agility of Tennis Athletes - Dahlia, Sari; Padli; Sari, Suci Nanda; Purnomo, Eko (STKIP Pasundan, 2025)
This study aims to determine the effect of ladder drill and cone drill training on improving the agility of tennis athletes at the Semen Padang Tennis Club. This study used an experimental method with a two-group pretest–posttest design, involving 10 athletes who were divided evenly into two groups using the ordinal pairing technique. Agility was measured using the Shuttle Run Test before and after 16 training sessions over five weeks. The data were analyzed using paired sample t-tests, independent sample t-tests, and N-Gain analysis. The results showed a significant difference between the pre-test and post-test scores (p < 0.05), indicating that both training methods effectively improved agility. The N-Gain score of 0.18 (18%), categorized as low effectiveness, indicates positive but limited improvement. In conclusion, ladder and cone drills significantly improve athletes' agility, although longer duration and higher training intensity are recommended for optimal results.